Biopesticides handbook - Nollet, Leo M. L., 1948-; Rathore, Hamir Singh (CRC Press, Taylor & Francis Group, 2015)
Offering a full spectrum and review of the range of organisms and organic products that may be used in the biological control of insects, this book discusses the uses and abuses of biopesticides that have been in circulation for more than 50 years, as well as more recent advances in this area. It describes the metabolism of these biopesticides and offers the best mode of action to prove environmental safety, detailing the present status of biopesticide residue in foodstuffs, soil, and water.